TRANSFORMASI PERGURUAN TINGGI ISLAM NEGERI DI INDONESIA: DARI SEJARAH KELEMBAGAAN HINGGA PARADIGMA KURIKULUM MODERN - Nabilatuz Zahra; Qonita Yuhanidz; Sutrimo Purnomo (PROGRAM STUDI PAI STIT TANGGAMUS, 2026)
This study aims to analyze the transformation of Islamic higher education institutions in Indonesia, particularly the institutional change from the State Islamic Institute (IAIN) to the State Islamic University (UIN), as well as its implications for the modern curriculum paradigm. This study uses a qualitative approach with a literature study method through the analysis of various relevant scientific literature. The results of the study show that the transformation from IAIN to UIN is a response to the problem of the dichotomy of knowledge between religious sciences and general sciences, as well as an effort to adapt to the demands of globalization and the development of knowledge. This transformation not only impacts changes in institutional structure but also encourages the emergence of a curriculum paradigm that is integrative, interdisciplinary, and contextual. In addition, UIN serves as a representation of the development of modern Islamic educational civilization in Indonesia. Nonetheless, there are still various challenges faced, such as limitations in the quality of human resources and institutional strengthening. Therefore, a sustainable development strategy is needed so that Islamic universities are able to increase competitiveness at both the national and global levels